2014
DOI: 10.1016/j.gca.2013.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Stable bromine isotopic composition of methyl bromide released from plant matter

Abstract: Methyl bromide (CH3Br) emitted from plants constitutes a natural source of bromine to the atmosphere, and is a component in the currently unbalanced global CH3Br budget. In the stratosphere, CH3Br contributes to ozone loss processes.Studies of stable isotope composition may reduce uncertainties in the atmospheric CH3Br budget, but require well-constrained isotope fingerprints of the source end members. Here we report the first measurements of stable bromine isotopes (δ 81 Br) in CH3Br from abiotic plant emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The CH 3 Br concentration in northern Sweden was 2-3 times lower than in the Stockholm area, possibly indicating industrial contamination of the latter area. CH 3 Br emissions from plants are about 2 ‰ depleted in 81 Br relative to bromine in the plant (Horst et al 2014). (Fietzke and Eisenhauer 2006;Krabbenhöft et al 2009;Neymark et al 2014).…”
Section: Brominementioning
confidence: 99%
“…The CH 3 Br concentration in northern Sweden was 2-3 times lower than in the Stockholm area, possibly indicating industrial contamination of the latter area. CH 3 Br emissions from plants are about 2 ‰ depleted in 81 Br relative to bromine in the plant (Horst et al 2014). (Fietzke and Eisenhauer 2006;Krabbenhöft et al 2009;Neymark et al 2014).…”
Section: Brominementioning
confidence: 99%
“…Further at the Abisko site also soil-air samples were collected to determine isotopic fingerprinting and the importance of this source. The results obtained by Horst et al (2013) and indicated that, overall, the air samples showed similar δ 81 Br values for both field studies ranging from −0.47 to +1.75 ‰ versus SMOB for Stockholm samples and −0.14 to +0.48 ‰ versus SMOB for Abisko samples. However, in Stockholm the δ 81 Br range was larger and the mixing ratios of CH 3 Br were higher (14.4 ± 2.1 pptv) whereas for the Abisko samples the mixing ratios (9.8 ± 3.1 pptv) were statistically indistinguishable from global background (8 pptv).…”
Section: Brominementioning
confidence: 63%
“…The first bromine isotope measurements of atmospheric CH 3 Br samples were reported by Horst et al (2013) and . They used the method developed by Thornton et al (2013) to extract enough CH 3 Br from atmospheric samples from sites near Stockholm (an urban site) and Abisko (a rural site) in Sweden.…”
Section: Brominementioning
confidence: 99%
See 1 more Smart Citation
“…Apart from carbon isotope analysis, hydrogen isotope 10 measurements have been demonstrated for CH3Cl (Nadalig et al, 2013;Keppler et al, 2018;Jaeger et al, 2018). For CH3Br bromine isotope analysis was presented in two studies (Horst et al, 2013;Horst et al, 2014).…”
Section: Introductionmentioning
confidence: 99%